Izvor acetilholinesteraze v živčno-mišičnem stiku sesalca - Jevšek, Marko (Medicinski razgledi, 2002)
The molecular mechanisms underlying synaptic formation are one of the central themes of modern neuroscience. The best-established role of acetylcholinesterase (AChE) is the termination of signal transmission in the neuromuscular junction (NMJ) and other cholinergic synapses by catalyzing hydrolysis of acetylcholine. Most of the AChE in the NMJ is bound to the specialized basal lamina located between the presynaptic membrane contributed by the nerve ending and the postsynaptic membrane belonging to skeletal musclefiber. Both cells can therefore be a source of synaptic AChE. Current evidence strongly supports a muscular origin for synaptic AChE; however, the possibility of neural origin has never been eliminated and is supported by another line of evidence. The objective of this work was to study the origin of synaptic AChE at the earlier stages of the formation of mammalian NMJ underin vitro conditions. At least part of the synaptic AChE found in the NMJ at the earlier stages of its formation is contributed by the motor neuron. In our study, an in vitro model was employed in which human muscle was co-cultured with the explants isolated from embryonic rat spinal cord. In these co-cultures the motor neurons originate from the rat spinal cord explants and form differentiated and long-lived NMJs with human muscle fibers.By using species-specific antibodies against human and rat AChE, respectively, we were able to distinguish between AChE of muscle (human) and neural (rat) origin. Species specificity of anti-AChE antibodies was tested byWestern blotting. Phase-contrast microscopy and fluorescent identification of acetylcholine receptors were used for visualization of the NMJs. (Abstract truncated at 2000 characters).
Keywords: Acetilholinesteraza; Acetylcholinesterase; Celične kulture; Neuromuscular Junction; Mišica skeletna; Muscle, Skeletal; Živčnomišični stik; Innervation; Anatomy And Histology; Elektroforeza, poliakrilamid gel; Cells, Cultured; Imunohistokemija; nevrobiologija; Immunohistochemistry; Electrophoresis, Polyacrylamide Gel; sinapse; živčno mišični stik; celične kuture; molecular biology; molekularna biologija; sesalci